Vibration Behavior and Reinforcement Effect Analysis of the Slab Track-Subgrade with Mud Pumping under Cyclic Dynamic Loading: Full-Scale Model Tests - Junjie Huang; Qian Su; Wei Wang; Xun Wang; Huiqin Guo (Shock and Vibration)
Mud pumping occurring in the subgrade bed can gradually deteriorate the performance of the slab track-subgrade, negatively affecting the comfort and safety of high-speed railway. In this paper, a full-scale model of the slab track-subgrade was established to analyze the vibration behavior of the model in normal condition and before and after mud pumping reinforced, as well as the reinforcement effect of mud pumping using low-viscosity epoxy resin. The research results show that the vibration acceleration and displacement and the settlement of the model in normal condition stabilize gradually with the increasing number of loading cycles. Under the upper layer of the subgrade bed saturated by water, mud pumping occurs in the subgrade bed as soon as the second loading stage reaches to 3.0 × 104 cycles, and the deterioration of mud pumping increases gradually with the increasing number of loading cycles. Moreover, a large volume of slurry composed of water and fine particles is squeezed out of the subgrade bed after the model is subjected to the second cyclic loading stage of 2.0 × 106 cycles, causing contact loss between the concrete base and the subgrade bed, which makes the acceleration and displacement of the concrete base increase abnormally compared with the model in normal condition, as well as the cumulative settlement of the subgrade bed. The model with significant mud pumping in the upper layer of the subgrade bed was reinforced by using low-viscosity epoxy resin. This effectively controlled the abnormal acceleration and displacement of the concrete base and restored the support capability of the subgrade bed for the concrete base of the slab track structure.